Trends in the utilization of nuclear medicine technology in Jamaica: Audit of a private facility - Kennedy-Dixon, Tracia-Gay; McDonnough, Karlene; Reid, Marvin; Gossell-Williams, Maxine (World Journal of Nuclear Medicine, 2021)
This study sought to evaluate the types and frequencies of nuclear medicine studies that were carried out at a privately-run nuclear medicine facility in Kingston, Jamaica. Previous studies of this nature have not been done among this population, therefore the researchers sought to gather data which may prove to be useful for the growth of nuclear medicine practice in Jamaica. The study was a nonexperimental, retrospective study which involved an assessment of the records of all nuclear medicine patients who received a radiopharmaceutical during January 01, 2017, to December 31, 2018. The data extracted included age, gender, radiopharmaceutical administered, indication for study, and impression from scan. The total number of nuclear medicine scans that were carried out at the facility for the 2-year period was 3756. Of this number, 1889 (50.3%) were male and 1866 (49.7%) were female, with the age ranging from 3 months to 100 years. The types and frequencies of the most frequently occurring studies conducted were bone (2116, 56.3%), renal (867, 23.1%), thyroid (307, 8.2%), and lung (254, 6.8%). Patients aged 60 years and over accounted for the majority of the bone scans (1353/2116). The age group 26–59 years accounted for most of the scans of the lung (123/254), thyroid (209/307), parathyroid (34/65), and whole body (26/34). Patients under 12 years of age accounted for the majority of the renal (596/867), gastrointestinal (22/26), and hepatobiliary (16/28) scans. The audit of this private facility reflects the documented demand on the International Atomic Energy Agency database for Latin America and the Caribbean, and demonstrates the need for continuity of this specialized service in our population.
Keywords: International Atomic Energy Agency; Jamaica; nuclear medicine; radiopharmaceuticals; trends